Talkout : Protecting mental health application with a lightweight message encryption - Gavin Teo Juen (2022)
The rise of technology and the Internet has changed how people communicate in society and virtual counselling development since the 1970s. It offers an effective way to seek psychotherapy and consultation services without physically presented by exploiting accessibility, ease of use, comfort and convenience of Internet features. However, the increased security breaches of recent mental health applications that leaked the patient's profile. This project proposed a virtual mental health mobile application, called TalkOut, with a lightweight message encryption algorithm to protect patient's profile, conversation messages and treatment history. The project objectives includes:(i) To investigate lightweight message encryption algorithms by benchmarking their efficiency in terms of computation speed and generated cipher text size; (ii) To design and develop the TalkOut mobile application with lightweight message encryption by using prototype software development model.; and (iii) To evaluate the usability performance of the developed proposed TalkOut mobile application using System Usability Scale (SUS) approach. Questionnaire and interview methods is used to gather user's requirement from campus students and campus counsellors. The investigation of lightweight message encryption algorithms is conducted with systematic quantitative literature and experiment implementation in Java and Android running environment. The outcome of this project provides an alternative for campus students to seek psychotherapy and consultation services and sharing platform, especially during distance online learning and covid-19 pandemic.